The Italian way to intercultural education: innovation and resistance - Bussotti, L. (Foro de Educación, 2017)
This article analyses a new phenomenon, which the Italian educational system has been facing: the growing presence of foreign students in Italian schools and the transition towards intercultural education. Even though both international and domestic factors greatly contributed to such changes, the article focuses exclusively on the domestic factors. Two issues are considered the most important. The first is the presence of «foreigners» in Italian classrooms and the second is the fall of the old political system (known as the First Republic). The article seeks to show how the Italian educational system dealt with this new challenge. We believe that it is possible to speak of an original Italian approach to intercultural education and that this model, which was introduced without any kind of planning by Italian institutions, is currently showing serious limitations. These limitations are evident when one looks at the profound differences in school performances between Italian and foreign students and at the substantially higher concentration of foreign students in vocational schools rather than general high school, which in turn leads to lower enrolment rates in academia. We use a multidisciplinary methodological approach. This approach is based on a sociological, philosophical and historical analysis of innovations and highlights the strong aversion to multiculturalism that pervades the Italian school system.